A cost savings analysis of asynchronous teledermatology compared to face-to-face dermatology in Catalonia - Josep Vidal-Alaball; Josep Lluís Garcia Domingo; Francesc Garcia Cuyàs; Jacobo Mendioroz Peña; Gemma Flores Mateo; Joan Deniel Rosanas; Glòria Sauch Valmaña (BMC, 2018)
Abstract Background A teledermatology pilot scheme was first conducted in the town of Manresa (Barcelona) in the summer of 2010. The clinical success of the scheme prompted its expansion to the whole county of Bages in 2011 and to the adjacent county of Berguedà in 2012. In the teledermatology service, primary care physicians take a photograph of the lesion and attach it to the electronic medical records of the patient together with a brief clinical account. In the referral hospital, the consultant dermatologists access the electronic medical records, review the images and suggest a treatment or action plan. Next, the primary care physicians review these recommendations and call the patient to report the results. This whole process is usually completed in less than 5 working days. Methods A cost saving analysis comparing teledermatology with dermatology face-to-face visits was performed in the county of Bages measuring the cost difference attributable to visits saved. Results The estimated added costs of the teledermatology service during 2016 amounted to 61,870 €. For the same period, the estimated costs of traditional outpatient dermatology services were of 113,034 €. This represents savings of 51,164 € per year. After subtraction of societal costs, the savings equal 10,350 € per year. Conclusions Using a teledermatology service instead of face-to-face dermatology consultations could save 51,164 € per year (11.4 € per patient visited) in the county of Bages. Societal savings are the most significant.